Transgenic over-expression of slit2 enhances disruption of blood-brain barrier and increases cell death after traumatic brain injury in mice. (19th September 2016) - Li, Shuai; Li, Hang; He, Xiao-fei; Li, Ge; Zhang, Qun; Liang, Feng-ying; Jia, Huan-huan; Li, Jiang-chao; Huang, Ren; Pei, Zhong; Wang, Li -jing; Zhang, Yu
Highlights: Two-photon microscopy was used to examine the role of slit2 in micro TBI (traumatic brain injury). BBB (Blood Brain Barrier) was damaged in the slit2 over expression mice at the acute stage of micro TBI. Cell death was accelerated in the slit2 over expression mice in micro TBI. Abstract: Traumatic brain injury (TBI) is the leading cause of mortality and disability among male adolescents and young adults; and mild traumatic brain injury is the most common type of traumatic brain injury. The disruption of blood-brain barrier (BBB) plays an important role in brain trauma. Previously, we have found that slit2, a member of slit protein family, increases permeability of BBB. In the present study, we examined the role of slit2 in the pathogenesis of mild TBI in a mouse model of micro TBI. Rhodamine BandPI (PropidiumIodide) staining were used to detect the permeability of BBB and cell death, respectively. The leakage of Rhodamine B and cell death were significantly increased in Slit2-Tg mice than in C57 control mice after micro TBI. The present results suggest that over expression of slit2 plays a detrimental role in the pathophysiology of mild TBI.